Research of structure and formation of nodular graphite inclusions in ductile cast iron - Ivanov, Valerii; Pirozhkova, Valentina; Lunеv Valentin (Eastern-European Journal of Enterprise Technologies, 2016)
A set of research of nodular graphite inclusions in ductile cast iron was carried out, including micrographic, x-ray and petrographic methods. Petrographic method has more possibilities and allows conducting research not only in the reflected but also in the transmitted light, to determine the structure and composition of graphite inclusions in the cases where other, even the most accurate methods, cannot apply. Based on the metallographic, petrographic and X-ray research, we introduced a new mechanism of formation of nodular shaped graphite in ductile cast iron. It is due to the simultaneous formation of a gas bubble, supply channel and its base – the mouth – graphite with a cavity inside that form a single system. We identified three morphological varieties of graphite, formed during different periods of changes in the physical–chemical conditions of liquid cast iron: in the moment of interaction of magnesium with carbon monoxide – clear-cut hexagonal; during the period of disproportionation of carbon monoxide in the volume of the gas bubble − aggregates of crystals of various shapes; during the "tempering" of carbon monoxide – film (cryptocrystalline). It was found that a full filling-up of the total volume of a gas bubble by graphite is carried out in three stages: the first two stages – by primary graphite, which deposits on the inner shell of the bubble, starting from the periphery to the centre, then it forms a nodular shape of graphite and the third and final – by secondary film graphite, distributed from the centre to the periphery. The obtained results will make it possible to take into account the peculiarities of the formation of nodular shaped graphite inclusions when designing technological processes of obtaining castings for various purposes, to determine the values of modifying additives, and, ultimately, to control the morphology of graphite phase in ductile cast irons.